Strengthening Character Education: The Role of Teachers in Improving the Morality of Students in the 5.0 Era - Agustang, A. Dody May Putra; Anggraeni, Nurul (Jurnal Pengabdian Masyarakat Bestari, 2024)
Teachers as educators will always face several challenges in teaching students. Especially in today's developments or the 5.0 era, one of which is that the morality of students is increasingly fading. This is a challenge for a teacher as well as a threat to future education if morality in this country disappears and no longer reflects the Pancasila values ​​that exist in Indonesia.